Voltage sag mitigation by optimizing the location of distributed generation using genetic algorithm for three distributed generation types - Ahmed Mohamed Abdrabou Ahmed, 1972- (Johor Bahru, Johor: Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2014